RELATIONSHIP OF CLASSICAL AND NON-CLASSICAL RISK FACTORS WITH GENETIC POLYMORPHISM OF PON 1 RELEVANT TO CORONARY ARTERY DISEASE - Kaman, Dilara; Ilhan, Necip; Metin, Kerem; Akbulut, Mehmet; Ustundag, Bilal (John Wiley & Sons Inc, 2009)
[Abstract Not Available]